Analisis Transaksi Jual Beli Sawit di Desa Kuala Keritang Kabupaten Indragiri Hilir Provinsi Riau Ditinjau Menurut Etika Bisnis Islam - Arif Rahman; Eja Armaz Hardi; M. Maulana Hamzah (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study examines two main issues related to palm oil trading transactions in Kuala Keritang Village, Indragiri Hilir Regency, Riau Province. The first issue concerns the analysis of pricing mechanisms in palm oil trading, while the second focuses on the review of Islamic business ethics in such transactions. The objective of this research is to understand in detail how the price determination system operates in the local palm oil market and to assess the extent to which these trading practices align with the principles of Islamic business ethics. To address these issues, a qualitative descriptive method was employed. This approach was chosen because it allows for a comprehensive description of facts, data, and trading mechanisms while providing space for critical analysis in relation to Islamic values. Data were obtained through observation, interviews, and documentation, which were then described, analyzed, and discussed in order to answer the research questions thoroughly. The findings indicate that, in general, palm oil trading practices in Kuala Keritang Village are similar to other common trading systems, but they differ in terms of price-setting mechanisms. In practice, the price of palm oil is largely determined by buyers based on market conditions, which often creates injustice for farmers as sellers. From the perspective of Islamic business ethics, this practice does not fully comply with the principles of fairness, honesty, and mutual benefit, which are essential foundations of Islamic economic transactions. The study concludes that violations of Islamic business ethics principles, particularly regarding fairness in pricing, still occur in palm oil trading within the village. Therefore, improvements are needed in the transaction system so that palm oil trading in Kuala Keritang can be carried out in accordance with sharia principles, ensuring justice and mutual benefit for both sellers and buyers.